A 10 GHz Compact Balun with Common Inductor on CMOS Process - Chatrpol Pakasiri; Jian-Long Xu; Sen Wang (Electronics, 2023)
This paper presents a compact balun with a common inductor design. The design used Wilkinson-type balun topology with modified lumped transmission lines and a common inductor to realize circuit size reduction on a lossy CMOS process. Measurements of the prototype chip had a reflection coefficient below 17.8 dB at all ports, an insertion loss of 1.98 dB, and an isolation of 16.8 dB. The chip size was only 0.025λ0 × 0.034λ0.
Keywords: Microwave Engineering and Waveguides; Radio Frequency Integrated Circuit Design; Electromagnetic Compatibility and Noise Suppression